Servant leadership and employee outcomes: the moderating role of subordinates' motives. Issue 5 (2nd September 2016) - Donia, Magda B.L.; Raja, Usman; Panaccio, Alexandra; Wang, Zheni
Abstract : Drawing from implicit leadership theories we advance servant leadership theory by examining moderating mechanisms that explain under what conditions servant leader behaviours impact followers in organizations. Specifically, we focused on the moderating role of subordinates' motivational orientations— prosocial values or impression management motives— in relationships between servant leadership behaviours and job satisfaction, as well as subordinate organizational citizenship behaviours (OCBs). Using time-lagged data collected from 192 supervisor-subordinate dyads, we found that servant leadership was positively associated with employees' job satisfaction, but not significantly related to their performance of OCBs. We also found evidence that subordinates' motives moderate the relationships between servant leadership and outcomes. Specifically, employees high on impression management experienced lower levels of job satisfaction than their lower scoring counterparts. Our findings suggest that servant leadership may not be equally beneficial for all followers. We discuss implications for theory and practice.